The Effect of Career Development and Work-Life Balance Programs on Employee Retention with Motivation as an Intervening Variable at PT PLN (Persero) ULP Kotanopan - Rahmat Akbar Siregar; Mesra B (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to assess how career development initiatives and work-life balance impact employee retention, with motivation as an intermediary variable at PT PLN (Persero) ULP Kotanopan. Quantitative methods were used through a survey, with a sample of 54 employees. The analysis used Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that motivation significantly and positively influences employee retention. Furthermore, career development initiatives and work-life balance were shown to significantly increase employee motivation. Although career development initiatives did not have a significant direct effect on retention, they did influence it indirectly through motivation. Conversely, work-life balance directly and positively influences employee retention, as well as through motivation. Thus, motivation is an important intermediary factor in increasing employee retention. These results are expected to guide management in developing HR policies to improve employee retention.